A model of depression - GRAY, P. (PSL Quarterly Review, 2013)
Some economists suggest that macroeconomic theory is incomplete because it has neglected to construct a model of instability. The author contends that a theory of depression must provide information on an economy's ability to resist depressions most of the time, and yet have an innate capacity to slide either slowly or rapidly into them periodically; the role of financial crisis and the ability of the economy to revive must also be explained. The author builds a model that exhibits these capacities and suggests that flight from the dollar may present a great threat to world economic stability. JEL: E17, G01